Leadership of Women Scholars in The Tradition of Pesantren in Madura: A Study on The Transformation of Patriarchy to Matriarchy in Pesantren - Andri Sutrisno (Institut Attanwir Bojonegoro, 2024)
In the tradition of pesantren in Madura, usually the leaders and caregivers of islamic boarding schools are often dominated by patriarchy (kyai leadership), this is undeniable because patriarchy has become a tradition of islamic boarding schools. It can be proven, that when there is a change of leadership and caregivers of the pesantren, it must be dominated by a man. However, from the presence of many islamic boarding schools in Madura, there is an al-huda islamic boarding school in pamekasan where the leader is a woman (matriarchy). As for this research, it uses a qualitative approach with the type of field research. Meanwhile, data collection techniques use observation, interview and documentation techniques. The data analysis technique uses data reduction, data presentation and drawing conclusions. So the result of this research is the transformation of patriarchy to matriarchy in the al-huda islamic boarding school through family deliberations, having a clear vision and mission motivation, having broad scientific insight and being able to face problems well.